Alpha-mangostin improves glucose uptake and inhibits adipocytes differentiation in 3T3-L1 cells via PPAR gamma, GLUT4, and leptin expressions - Bakhtiar, M. Taher; Mohamed Amiroudine, Mohamed Zaffar Ali; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari; Kaderi, Mohd Arifin; Ahmed, Qamar Uddin; Zakaria, Zainul Amiruddin (Hindawi Publishing Corporation, 2015)
Obesity has been often associated with the occurrence of cardiovascular diseases, type 2 diabetes, and cancer. The development of obesity is also accompanied by significant differentiation of preadipocytes into adipocytes. In this study, we investigated the activity of alpha-mangostin, a major xanthone component isolated from the stem bark of G. malaccensis, on glucose uptake and adipocyte differentiation of 3T3-L1 cells focusing on PPAR gamma, GLUT4, and leptin expressions. alpha-Mangostin was found to inhibit cytoplasmic lipid accumulation and adipogenic differentiation. Cells treated with 50 mu M of alpha-mangostin reduced intracellular fat accumulation dose-dependently up to 44.4% relative to MDI-treated cells. Analyses of 2-deoxy-D-[H-3] glucose uptake activity showed that alpha-mangostin significantly improved the glucose uptake (P < 0.05) with highest activity found at 25 mu M. In addition, alpha-mangostin increased the amount of free fatty acids (FFA) released. The highest glycerol release level was observed at 50 mu M of alpha-mangostin. qRT-PCR analysis showed reduced lipid accumulation via inhibition of PPAR gamma gene expression. Induction of glucose uptake and free fatty acid release by alpha-mangostin were accompanied by increasing mRNA expression of GLUT4 and leptin. These evidences propose that alpha-mangostin might be possible candidate for the effective management of obesity in future.